ON A LARGE SUNFISH RANZANIA TYPUS FROM THE SOUTHWEST COAST - Ebenezer, I P; Joel, J Jerold (Indian Journal of Fisheries, 2011)
A sunfish (or trunkfish), Ranzania typus, measuring 616 mm total lengthand a maximum depth of 310 mm was caught at Erayumanthurai on the southwestcoast (Kanyakumari district, Tamil Nadu) on 2-3-1984 in a shore seine.The gear had operated a distance of 1 km from the shore, up to a depth of 22m. Coloured bluish, tending towards dark above and to silvery below, it had asmooth skin with small hexagonal plates. Six streaks of lighter colour withdarker borders, emanated from near the dorsal margin between the snout andthe gill slit, curved downwards to the ventral profile. The posterior threestreaks were branched and contained dark spots, mostly round. Lips were producedforwards beyond teeth as a funnel, closing in a vertical slit.